Small size sigma-delta analog to digital converter - Rocha, J. G. (2002)
This report describes the analog to digital converter for an image sensor, implemented in a standard CMOS process. The image sensor, after coated with a scintillator material, can acquire x-rays images. Since it uses standard CMOS technology, the digital circuits of control and signal processing can be integrated into the same chip. The analog to digital convertion is based in a sigma delta approach, being implemented inside each pixel.